Legal Protection of Health Workers on the Installation of Mechanical Ventilation of Covid-19 Patients in Hospitals - Suwito Suwito; Puguh Aji Hari Setiawan; Gradios Nyoman Tio Rae (Jurnal Indonesia Sosial Sains, 2024)
Corona Virus Disease-2019 (Covid-19) is a disease that causes an epidemic with a high number of deaths and morbidity in Indonesia. Covid-19 sufferers often experience respiratory failure, so they need to receive mechanical ventilation assistance. This research aims to find out the rules for legal protection for health workers in the act of installing mechanical ventilation for Covid-19 patients in hospitals and to find out the implementation of legal protection. This type of research is normative juridical based on a legal approach. Data collection is based on literature study, taken from legislation, research results and literature books. The results of the research found that the provision of health services was carried out responsibly, safely, of good quality and evenly and non-discriminatory. The position faced by medical personnel or health workers is sometimes problematic because installing mechanical ventilators for Covid-19 patients from a criminal law perspective is a mistake if it is done outside of their authority, even though the medical personnel or health workers are dealing with the function and task of carrying out actions. for patient safety which is of course tied to the Hippocratic Oath as an ethical and moral basis. The suggestion in this research is that the government must provide legal protection to medical personnel whose rights are not fulfilled by policy organizers, even though their obligations have been fulfilled by health personnel.